Étude phytochimique et évaluation de l’activité antioxydante des feuilles de Gymnema sylvestre provenant de la région de Mostaganem - SAHRAOUI, Nabila meriem; OULD AISSA, Hadja khouloud (My University, 2025)
This study focuses on the phytochemical characterization and the evaluation of the antioxidant and anti-inflammatory activities of Gymnemasylvestre leaves collected from the Mostaganem region (Algeria). Gymnemasylvestre is a well-known medicinal plant traditionally used for its antidiabetic and metabolic-regulating properties. The primary objective of this research is to identify bioactive compounds and assess their biological potential through various in vitro assays. Qualitative phytochemical screening revealed the presence of several classes of secondary metabolites, including polyphenols, flavonoids Quantitative determinations were performed using standard spectrophotometric methods:  Total polyphenol content was measured using the Folin–Ciocalteu method and expressed as mg gallic acid equivalents (GAE) per gram of extract.  Total flavonoid content was determined by the aluminum chloride method and expressed as mg quercetin equivalents (QE) per gram. The antioxidant activity of the leaf extracts was assessed using two complementary methods:  The DPPH radical scavenging assay (2,2-diphenyl-1-picrylhydrazyl) to evaluate free radical neutralization capacity.  The FRAP assay (Ferric Reducing Antioxidant Power) to measure the reducing power of the extracts. The results indicated that methanolic extracts exhibited higher levels of phenolic compounds and stronger antioxidant activity compared to aqueous extracts. A positive correlation was observed between polyphenol/flavonoid content and antioxidant efficacy, confirming the significant role of these compounds in oxidative stress reduction. Additionally, the anti-inflammatory activity was evaluated in vitro using protein denaturation inhibition assays, specifically targeting bovine serum albumin (BSA) and protease enzymes. The findings revealed dose-dependent inhibition, highlighting a notable anti-inflammatory effect, particularly in methanolic extracts. In conclusion, Gymnema sylvestre leaves from the Mostaganem region are rich in bioactive phytochemicals and demonstrate significant antioxidant and anti-inflammatory potential. These findings support the traditional use of the plant and underscore its promise as a natural source for therapeutic and nutraceutical applications.
Keywords: DPPH; FRAP; Gymnema sylveestre; Antioxidant; Anti-inflammatory